THE EFFECTS OF GLOBALIZATION ON LOCAL COMPANY IN MANADO: A CASE STUDY OF CV. CENTRAL BUKIT MORIA MANADO - Rembet, Edelways Cheryl Sandrina; Saerang, David Paul Elia; Rumokoy, Farlane (FEB Universitas Sam Ratulangi Manado, 2014)
Globalization is a leading concept which has become the main factor in business life during the last few decades. This phenomenon affects the economy, business life, society and environment in different ways, and almost all corporations have been affected by these changes. On a local level, globalization has dramatically changed the nature of business. Many smaller, local companies have been pushed out of business by their TNC competitors. It is important to know the effects of globalization on local companies in order to create a management strategy the help the local company survive from the power of globalization. The research is conducted in qualitative research design and the data are gathered with unstructured interviews with four respondents. The data are analyzed and it is found that there are two kinds effects of globalization that affect the company. The positive effects and the negative effects and the company strategies to face the globalization. Keywords: globalization, local company, management strategy